2007
DOI: 10.1007/s00394-007-0655-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and C-reactive protein in heart failure: an anti-inflammatory effect of magnesium administration?

Abstract: Oral Mg supplementation to HF patients significantly attenuates blood levels of CRP, a biomarker of inflammation. Targeting the inflammatory cascade by Mg administration might prove a useful tool for improving the prognosis in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 36 publications
2
39
1
1
Order By: Relevance
“…In contrast to observational studies that linked higher dietary magnesium intakes to lower concentrations of biomarkers of systemic inflammation (8,24), we observed a significant increase in IL-6 concentrations after magnesium treatment. IL-6 is a proinflammatory cytokine secreted by macrophages and T cells and is the major mediator of the acute-phase response (25).…”
Section: Tablecontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to observational studies that linked higher dietary magnesium intakes to lower concentrations of biomarkers of systemic inflammation (8,24), we observed a significant increase in IL-6 concentrations after magnesium treatment. IL-6 is a proinflammatory cytokine secreted by macrophages and T cells and is the major mediator of the acute-phase response (25).…”
Section: Tablecontrasting
confidence: 99%
“…Because elevated IL-6 concentrations may provide an early indicator of acute inflammation, the observed increase in IL-6 concentrations may reflect a variation because of unmeasured underlying acute infection disproportionately present in the magnesium treatment by chance, although we do not have recorded measurements of transitory illness to confirm this explanation. Very few randomized trials have examined the effects of magnesium supplementation on systemic inflammation in overweight individuals (24), and our findings suggest a need for further investigation in larger trials.…”
Section: Tablementioning
confidence: 78%
“…The highest concentrations of magnesium were found in the leaves of Capraria biflora (199 mg/100 g), Mikania glomerata (159 mg/100 g) and Datura stramonium (297 mg/100 g), plants used in folk medicine as an anti-inflammatory. Studies have shown that oral Mg supplementation to heart failure patients significantly reduces blood levels of C-reactive protein, a biomarker of inflammation (Almoznino-Sarafian et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In this publication we discussed amply the role of Se in inflammation. Data concerning Mg and inflammation can be found in the literature [47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The initial invitation of the Editors of this book was indeed to elaborate on these pathophysiological connections.…”
Section: Discussionmentioning
confidence: 99%